VARIASI RELASI MAKNA DALAM BAHASA ARAB: ANALISIS SINONIMI PADA BERITA ONLINE AL-JAZEERA - Muhammad, Alfa; Yusuf, Kamal (An-Nas, 2024)
The aim of this research is to describe the use of synonyms in technology news in the online media al-Jazeera. This type of research is descriptive qualitative. The object of this research is an analysis of synonyms found in technology news in the online media al-Jazeera. Data collection in this research used note-taking and library techniques. The note-taking technique in question is recording relevant data that is in accordance with the research goals and objectives. Library techniques are data collection based on written sources that reflect synchronous language use. Data that is relevant to the research objectives is then tapped and written or recorded on the data along with the data source. Based on the results of data analysis, it can be concluded that the use of synonyms is characterized by the existence of an equivalent meaning relationship between certain lingual units and other lingual units in discourse. In this research, types of word-to-word synonymy and sentence-to-sentence synonymy were found. Keywords: Synonymy, Meaning Relations, Online Media, Technology News